Analysis of Accounting Treatment of Fixed Assets - Burhanudin, Burhanudin; Iskandar (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2024)
The purpose of the study is to determine the suitability of the application of fixed asset accounting in the East Kalimantan Police Brimob Unit with PSAP 07 in Government Regulation No. 71 of 2010. Using comparative analysis to compare the success of the applied accounting treatment. Quantitative data types. Secondary data sources. As a result of the research, the fixed assets belonging to the East Kalimantan Police Brimob Unit in the form of land, equipment and machinery, have not fully met PSAP 07. There is a difference in the value of fixed assets presented in several reports regarding fixed assets. However, for fixed assets in the form of networks and other fixed assets have met PSAP 07.The research objective is to determine the suitability of the application of fixed asset accounting at the East Borneo Police Mobile Brigade Corp with PSAP 07 in PP No. 71/2010. Using comparative analysis to compare the appropriateness of the accounting treatment applied. Quantitative data types. The secondary data. The results showed that the fixed assets belonging to the East Borneo Police Mobile Brigade Corp in the form of land, equipment and machinery, did not fully comply with PSAP 07. Differences in the value of fixed assets that were presented in several reports regarding fixed assets. However, fixed assets in the form of networks and other fixed assets have met PSAP 07